Thermal analysis study of polymer-to-ceramic conversion of organosilicon precursors - Galusek D.; Lenčéš Z.; Šajgalík P.; Riedel Ralf (Journal of Mining and Metallurgy. Section B: Metallurgy, 2008)
The organosilicon precursors attract significant attention as substances, which upon heating in inert or reactive atmosphere convert directly to oxide or non-oxide ceramics, like nitrides, carbides, carbonitrides, boroncarbonitrides, oxycarbides, alons, etc. In characterisation, and in study of conversion of these polymers to ceramics thermal analysis plays an important role. The degree of cross-linking of the polymer vital for achievement of high ceramic yield is estimated with the use of thermal mechanical analysis (TMA). Decomposition of polymers and their conversion to ceramics is studied by the combination of differential thermal analysis (DTA), differential scanning calorimetry (DSC) thermogravimetry(TG), and mass spectrometry (MS). The use of these methods in study of the polymer-to-ceramic conversion is illustrated by case studies of a commercially available poly(allyl)carbosilane as the precursor of SiC, and a poly(hydridomethyl)silazane as the precursor of SiCN.